Computer vision-based Bengali sign language to text generation - Tazalli, Tonjih; Liya, Sumaya Sadbeen; Aunshu, Zarin Anan; Hossain, Magfirah; Mehjabeen, Zareen (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.